Decision Support System Determines the Feasibility of Granting a General Practitioner License Using the Analytic Network Process Method (ANP) - Silvia, Sindy; Maulita, Yani; Syahputra , Siswan (Journal of Mathematics and Technology (MATECH), 2024)
There are differences in general practitioner practice licensing services because they have special attention that is directly related to the health and public health sectors. The Langkat Regency Investment and One-Stop Integrated Licensing Services Service (DPMPPTSP) has also experienced the development of the system, but it still has a weakness, namely if the applicant who wants to make a permit must come to the office to validate the permit that the customer wants to make without knowing whether whether the files brought by the customer will be valid or not. So we need a decision support system that can help decision makers to use data and solve existing problems. The Analytic Network Process (ANP) method is a method that is able to represent the level of interest of various parties by considering the interrelationships between existing criteria and sub-criteria. From the results of the trials carried out, it was found that the highest score was 2.4625, namely Dr. Frimaneti Z, Old Village Health Center Upt, and Dr. Setiadi Abdillah Pratama, UPT Puskesmas Tanjung Selamat.